Literature Review of Research Trends in the Development of Canva-Based Interactive Learning Media for Elementary Schools Between 2019-2025 - Ilahy, Wildan Qosid; Sholeh, Muh; Subali, Bambang; Widiarti, Nuni (Research, Training and Philanthropy Institution Natural Aceh, 2025)
This study explores how research has evolved regarding the use of Canva-based interactive learning media in elementary schools between 2019 and 2025. The growing need for creative, engaging, and user-friendly teaching tools-especially in light of rapid digital transformation in education-forms the core motivation behind this review. Canva, known for its intuitive design and ease of use, has gained traction among educators as a go to platform for developing visually appealing and interactive classroom materials. Using a Systematic Literature Review (SLR) approach, the study analyzed 20 peer-reviewed articles from reputable academic sources. Articles were selected based on criteria such as publication (2019-2025), relevance to Canva as a teaching tool, and focus on elementary education. The findings reveal a clear upward trend in the adoption of Canva to enhance student participation, conceptual understanding, and learning motivation. The media created through Canva tend to be highly visual, easily accessible, and adaptable across different instructional approaches, including thematic and project-based learning. These results highlight the growing importance of equipping teachers with the necessary training and encouraging the integration of Canva into classroom practice as part of broader educational innovation aligned with today's digital era.